(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Monetary items serve as an avenue for investment and provide a certain level of financial security to investors based on the risk-return profile of these products. Historically, traditional financial products in India were introduced by banks (like savings and credit accounts), Life Insurance Corporation (LIC), and the postal service (such as recurring deposits, National Savings Certificates, and Kisan Vikas Patra). However, with the advancement of the financial services industry in recent years, a range of new financial products have emerged including mutual funds, stocks, derivatives, life and non-life insurance plans (such as Unit Linked Investment Plans (ULIPs), pension plans, children’s education plans, etc.). Investment preferences vary from person to person, as each individual has a unique approach to investing influenced by personal circumstances. With an aim to generate significant returns over time and within certain risk levels, individuals invest in various financial products. This study seeks to explore the investment preferences of police officers from Thane district across different demographic factors.